The Role of Private International Law in Cross-Border Relations - Katarzyna Anna DADANSKA (Communications of International Proceedings, 2021)
The aim of the paper is to outline the role of private international law in cross-border relations. International traffic of individuals and international trade are the two areas that generate real-life situations connected with more than one legal system. The role and importance of private international law is presented in the context of selected cross-border relations. The research relies on the study of law method, and secondarily, on the historical method. The main focus of the paper is to analyze the goals of private international law, including the impact of conflict of law solutions on the process of harmonization and uniformization of legal systems across nation-states, in particular within the EU, and its effects: pursuit of integration, ensuring international justice in the area of private law through determining applicable law on the basis of factual relations; harmonization of private law; promotion of safe and secure international trade through private law; facilitation and support of cross-border private law relationships; and finally, protection of values and interests under national and EU substantive law. The author analyzed solutions to conflict of laws with respect to contracts, family maintenance and succession, focusing, in particular, on the parties’ freedom of choice with regard to applicable law, i.e. party autonomy.
Keywords: Private International Law; Conflict of Laws; Cross-Border Relationships; Child Support; Succession